The MIT Dictionary of Modern Economics. - Alexander, Gordon J.; Pearce, David W. (Journal of Finance, 1993)
The MIT Dictionary of Modern Economics is an up-to-date, authoritative reference designed primarily for students of business and other social sciences and ideal for anyone who wants a brief explanation of an economic concept or institution.In this fourth edition one entry in ten has been revised and one entry in twenty is new. Whereas the third edition increased the coverage of American institutions, this edition breaks new ground by including entries considered important from an Eastern European perspective. It also supplies comparative statistics on major economic variables for selected countries, describes the origins of widely used acronyms, and includes bibliographic references at the end of featured entries.The dictionary answers in a clear and concise way the enduring questions, which economists have considered for two centuries or more, as well as the issues of the moment, such as economic change in Europe, the problems of pollution, or the prospects for greater freedom of trade. With close to 2,800 entries it is comprehensive in its coverage of theory, national and international institutions, schools of thought, and important economists, including recent Nobel Prize winners.The dictionary was compiled initially by an experienced team of economists at Aberdeen University in the United Kingdom, and new authors have been recruited to provide international expertise, reflecting changes in the structure of the international economy. David W. Pearce, general editor, is Professor of Political Economy at University College, London.This fourth edition was prepared by John Cairns, Robert Elliott, Ian McAvinchey, and Robert Shaw, all of the Economics Department, University of Aberdeen.